2022
DOI: 10.1021/acsbiomaterials.1c01101
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage Repair Using Clematis Triterpenoid Saponin Delivery Microcarrier, Cultured in a Microgravity Bioreactor Prior to Application in Rabbit Model

Abstract: Cartilage tissue engineering provides a promising method for the repair of articular cartilage defects, requiring appropriate biological scaffolds and necessary growth factors to enhance the efficiency of cartilage regeneration. Here, a silk fibroin (SF) microcarrier and a clematis triterpenoid saponin delivery SF (CTS-SF) microcarrier were prepared by the high-voltage electrostatic differentiation and lyophilization method, and chondrocytes were carried under the simulated microgravity condition by a rotating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Clematis total saponins is the extract of Willingin, which can significantly inhibit inflammation, reduce oxidative stress damage, and protect chondrocytes from apoptosis, thereby promoting cartilage tissue damage repair, and has long been used to treat OA 132–134 . We prepared a silk fibroin microsphere loaded with wellingxian saponins that can carry chondrocytes, implanted it into a rabbit model of full‐thickness cartilage injury, and found that it showed good cartilage repair and no obvious vascular invasion at the regenerated cartilage site 135 …”
Section: Anti‐angiogenesis Strategies In Tissue Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…Clematis total saponins is the extract of Willingin, which can significantly inhibit inflammation, reduce oxidative stress damage, and protect chondrocytes from apoptosis, thereby promoting cartilage tissue damage repair, and has long been used to treat OA 132–134 . We prepared a silk fibroin microsphere loaded with wellingxian saponins that can carry chondrocytes, implanted it into a rabbit model of full‐thickness cartilage injury, and found that it showed good cartilage repair and no obvious vascular invasion at the regenerated cartilage site 135 …”
Section: Anti‐angiogenesis Strategies In Tissue Engineeringmentioning
confidence: 99%
“…[132][133][134] We prepared a silk fibroin microsphere loaded with wellingxian saponins that can carry chondrocytes, implanted it into a rabbit model of full-thickness cartilage injury, and found that it showed good cartilage repair and no obvious vascular invasion at the regenerated cartilage site. 135 Numerous TCM extracts that are used to treat cartilage injuries also possess anti-angiogenic effects, such as ginsenosides, 136 artemisinin, 137 dihydroartemisinin, 138 betaine, 139 and baicalin. 140 Notably, in the treatment of diseases with TCM, compound herbal formulations are often used as the main approach.…”
Section: Traditional Chinese Medicine Extractmentioning
confidence: 99%
“…Following the implantation of microcarrier–cell composites at the injury site of rabbit articular defects, the treatment groups exhibited cartilage‐like tissue repair. [ 78 ] Promising cell carrier–cartilage ECM‐derived particles have good cellular compatibility with adipose‐derived stem cells. Under mimic microgravity conditions in RCCS, MSCs differentiated into a chondrogenic phenotype with no need for exogenous growth factors.…”
Section: Scaffold‐based Tissue Engineering Under Microgravity Conditionsmentioning
confidence: 99%
“…Fibrin, a natural polymer, has good biocompatibility and morphological plasticity and is widely used in CTE [ 27 ]. Studies have shown that silk fibroin (SF) scaffolds loaded with CS can promote cartilage regeneration in a rabbit knee cartilage defect model [ 28 ]. SF, as a kind of biomaterial with good biocompatibility, degradability and modifiability, has been widely used in CTE.…”
Section: Introductionmentioning
confidence: 99%